1992
DOI: 10.1111/j.1523-536x.1992.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Survival of an Infant with a Birthweight of 345 Grams

Abstract: Infant survival with ever-decreasing birthweights is attainable with recent advances in maternal-fetal medicine and enhanced neonatal intensive care. We report a gestation complicated by severe chronic hypertension and fetal distress necessitating delivery at 26 1/7 weeks. The growth-retarded newborn weighted 345 g (12 oz) and survived with minimal sequelae despite a protracted and complicated neonatal course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Although a summary of the literature is beyond the scope of this article, these individual studies have been included in reviews of perinatal loss research (Dyregrov, 1990;Zeanah, 1989). Although care providers have attempted to establish weight and maturity-related guidelines for providing and withdrawing treatment (Allen et al, 1993;Davis, 1993;Whyte et al, 1993), these efforts are complicated by reported case studies of the few intact survivors within this population (Amato, 1992;Coccia, Pezzani, Moro, & Minoli, 1992;Ginsberg et al, 1992;Muraskas et al, 1992;Optiz et al, 1993;Sherer, Abramowicz, Bennett, Mercier, & Woods, 1992). Ethical dilemmas have evolved because of extremely high mortality rates for newborns weighing less than 500 g at birth, which have remained greater than 90% for the past decade (Davis, 1993;Hack & Fanaroff, 1986, 1988Hernandez, Offutt, & Butterfield, 1986;Hoffman & Bennett, 1990;Whyte et al, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a summary of the literature is beyond the scope of this article, these individual studies have been included in reviews of perinatal loss research (Dyregrov, 1990;Zeanah, 1989). Although care providers have attempted to establish weight and maturity-related guidelines for providing and withdrawing treatment (Allen et al, 1993;Davis, 1993;Whyte et al, 1993), these efforts are complicated by reported case studies of the few intact survivors within this population (Amato, 1992;Coccia, Pezzani, Moro, & Minoli, 1992;Ginsberg et al, 1992;Muraskas et al, 1992;Optiz et al, 1993;Sherer, Abramowicz, Bennett, Mercier, & Woods, 1992). Ethical dilemmas have evolved because of extremely high mortality rates for newborns weighing less than 500 g at birth, which have remained greater than 90% for the past decade (Davis, 1993;Hack & Fanaroff, 1986, 1988Hernandez, Offutt, & Butterfield, 1986;Hoffman & Bennett, 1990;Whyte et al, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, little is known about the responses of parents whose newborns weigh less than 500 g. Instead of focusing on the experience of parents, the literature has focused on outcome data and the ethical aspects of providing or withdrawing aggressive treatment for these newborns. One of these case studies (Sherer et al, 1992) received the attention of other professionals (Campbell, 1992;Guillemin, 1992;Paneth, 1992) and a parent of a premature infant (Harrison, 1992), who raised a number of ethical concerns that evolve from treatment decisions, including the perceived experimental nature of aggressive treatment for these newborns and the financial burden of care. Although care providers have attempted to establish weight and maturity-related guidelines for providing and withdrawing treatment (Allen et al, 1993;Davis, 1993;Whyte et al, 1993), these efforts are complicated by reported case studies of the few intact survivors within this population (Amato, 1992;Coccia, Pezzani, Moro, & Minoli, 1992;Ginsberg et al, 1992;Muraskas et al, 1992;Optiz et al, 1993;Sherer, Abramowicz, Bennett, Mercier, & Woods, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the past decade, innovations in antepartum fetal surveillance and neonatal intensive care have markedly improved the survival of premature infants, and low-ered the threshold of viability of normal fetuses to 24 weeks' gestation where survival is approximately 50%. 1 Furthermore, when evaluating birth weight as a criterion for survival in appropriately grown infants, those weighing 1250 grams or less at birth had survival rates of 62.1% to a high of 85.2% 2 and a weight limit of viability that has been suggested by other authors to be about 600 g. 3 During this same time period, there have been a number of reports in the medical literature of the remarkable survival of premature, extremely low-birthweight (ELBW) infants (birth weight less than 1000 g) with severe intrauterine growth restriction (IUGR), weighing as little as 280 to 390 g at 25 to 26 weeks' gestation, 4,5,6 which push the limits of viability even further. A significant percentage of IUGR fetuses die before birth.…”
Section: Introductionmentioning
confidence: 97%
“…However, by the time there are definitive signs of permanent brain damage, the initial resuscitative efforts have already been made and it often requires acts of commission to reverse them. While there have been calls for greater selectivity in the treatment of these very tiny infants [e.g., Campbell, 1992], the majority of neonatal caregivers remain committed to survival as the primary goal [Sherer et al, 1992].…”
Section: Cerebral Palsy and Maturity At Birthmentioning
confidence: 99%